Philosophies and pedagogies that shape an integrated engineering programme. Issue 1 (1st January 2019) - Mitchell, John; Nyamapfene, Abel; Roach, Kate; Tilley, Emanuela
ABSTRACT: Accredited engineering degrees call upon students to develop a wide range of knowledge and skills. These range from technical, scientific and mathematical knowledge, through to transferable skills such as communications, teamwork, business acumen and critical analysis. Through a faculty-wide curriculum development programme we have sought to implement cross-department teaching framework whereby a range of pedagogies are employed to deliver against core philosophies for a new way of teaching aimed at developing students' knowledge, skills and attitudes while meeting a diverse range of learning outcomes. We argue that is it vital that learning takes place in the context of authentic engineering problems and processes. In this paper, we look at the philosophies, pedagogies and outcomes of an educational-based project which creates a connected curriculum that joins distinct disciplines at key points during the students' education to provide preparation for, and experience of, professional engineering. It describes the motivation for change and described the implementation and impact of these approaches.